2021
DOI: 10.18488/journal.90.2021.81.26.34
|View full text |Cite
|
Sign up to set email alerts
|

Dual Cognitive Tasks Provoke Temporo-Spatial Gait and Anticipatory Postural Adjustments in Healthy Young Adults

Abstract: Usually, dual cognitive tasks require additional attention to maintain postural control during standing and walking. In certain pathologies or injuries, dual cognitive tasks, such as walking and speaking, can challenge the balance system, making certain gait deficiencies more apparent. The issue is identifying normal gait changes compared to gait impairments to understand better the impact cognitive tasks have on gait mechanics. Purpose: To identify changes in temporospatial gait parameters in healthy young ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that muscle activation for APAs is related to the primary motor cortex, supplementary motor areas, basal ganglia, and spinal cord (5). Many factors such as the type of perturbation created, the person's level, the static and dynamic conditions, virtual reality, dual cognitive tasks, and attention affect APAs (6)(7)(8). On the other hand, research has shown that stimulus-driven attention modulates the onset of APA (2,6).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that muscle activation for APAs is related to the primary motor cortex, supplementary motor areas, basal ganglia, and spinal cord (5). Many factors such as the type of perturbation created, the person's level, the static and dynamic conditions, virtual reality, dual cognitive tasks, and attention affect APAs (6)(7)(8). On the other hand, research has shown that stimulus-driven attention modulates the onset of APA (2,6).…”
Section: Introductionmentioning
confidence: 99%